Red foxes avoid apex predation without increasing fear. (17th June 2021) - Wooster, Eamonn I F; Ramp, Daniel; Lundgren, Erick J; O'Neill, Adam J; Wallach, Arian D
Abstract: Apex predators structure ecosystems by hunting mesopredators and herbivores. These trophic cascades are driven not only by the number of animals they kill, but also by how prey alter their behaviors to reduce risk. The different levels of risk navigated by prey has been likened to a "landscape of fear." In Australia, dingoes are known to suppress red fox populations, driving a trophic cascade. However, most of what we know of this relationship comes from circumstances where predators are persecuted, which can affect their social and trophic interactions. Utilizing camera traps, we monitored fox behavior when accessing key resource points used by territorial dingoes, in a region where both predators are protected. We predicted that foxes would avoid and be more cautious in areas of high dingo activity. Indeed, foxes avoided directly encountering dingoes. However, contrary to our expectations, foxes were not more cautious or vigilant where dingo activity was high. In fact, fox activity and scent-marking rates increased where dingo scent-marking was concentrated. Further, foxes were increasingly confident with increasing levels of conspecific activity. Our results suggest that responses to the threat of predation are more complex than fear alone. In socially stable conditions, it is possible that prey may develop knowledge of their predators, facilitating avoidance, and reducing fear. Abstract : Red foxes avoid dingoes but don't live in fear. In Australia, dingoes suppress populations of foxes, reducing their numbers and altering their behavior. We found that where dingoes and foxes are protected from humans, foxes avoid dingoes in both space and time, while behaving confidently. Foxes appear to benefit from the predictability of stable dingo packs and develop detailed knowledge of their patterns to best avoid them.